Political Interaction Between Farmer Groups and Village Government During Crop Failure Conditions: A Case Study of Sumber Suko, OKU - Fidatul Umahat, Ana; Imron, Imron; Andi Guna, Leo (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
Most farmers in Sumber Suko Village are small-scale and face economic challenges, hindering their capacity development. Recent harvest failures have exacerbated their plight, but instead of giving up, they persevere. The village government collaborates with farmer groups to address issues like pest infestation, adverse weather conditions, and fertilizer scarcity. This study delves into the dynamics between farmer groups and the village government during crop failures, aiming to grasp agricultural management principles and strategies for sustaining productivity despite setbacks. Employing descriptive qualitative methods such as observation, interviews, and documentation, the research purposefully selects data sources to capture both primary (interviews) and secondary (literature) information.Findings reveal a symbiotic relationship between farmer groups and the local government, bridging communities with governance. Some farmers are not only group members but also village officials, leveraging their roles to educate and empower peers through mentorship, training, and environmental awareness initiatives. These efforts identify hurdles and pave the way for more successful agricultural management in the face of adversity.